Posterior spinal fusion for adolescent idiopathic scoliosis and the impact of postoperative intravenous dexamethasone supplementation - Amy McIntosh; Emily Lachmann; Anne‐Marie Datcu; Christopher McLeod (Wiley, 2024)
Abstract Postoperative care pathways for adolescent idiopathic scoliosis patients undergoing posterior spinal fusion have demonstrated decreases in postoperative opioid consumption, improved pain control, and lead to decreased lengths of stay. Our objective was to implement postoperative steroids to reduce acute postoperative opioid consumption, pain scores, and length of stay. Dosing consisted of intravenous dexamethasone 0.1 mg/kg up to 4 mg per dose for a total of three doses at 8, 16, and 24 h postoperatively. As part of a quality initiative, we compared three cohorts of patients. The initial retrospective epidural cohort (EPI) (n = 59) had surgeon placed epidural catheters with infusion of ropivacaine 0.1% postoperatively for 18-24 h. Following an institutional change in postoperative care, epidural use was discontinued. A second cohort (n = 149), with prospectively collected data, received a surgeon placed erector spinae plane block and wound infiltration with a combination of liposomal and plain bupivacaine (LB). A third cohort (n = 168) was evaluated prospectively. This cohort received a surgeon placed erector spinae plane block and wound infiltration with liposomal and plain bupivacaine and additionally received postoperative dexamethasone for three doses (LB + D). Compared to the LB cohort, the LB + D cohort demonstrated statistically significant decreases in oral milligram morphine equivalents per kilogram at 0-24, 24-48, and 48-72 h. There was a statistically significant difference in median pain scores at 24-48 and 48-72 h in LB + D versus LB. The LB + D cohort's median length of stay in hours was significantly less compared to the LB cohort (52 h vs. 70 h, p < 0.0001). Postoperative intravenous dexamethasone was added to an established postoperative care pathway for patients undergoing posterior spinal fusion for idiopathic scoliosis resulting in decreased VAS pain scores, opioid consumption, and shorter length of stay.